2022
DOI: 10.3390/jcm11061525
|View full text |Cite
|
Sign up to set email alerts
|

Double Balloon Catheter (Plus Oxytocin) versus Dinoprostone Vaginal Insert for Term Rupture of Membranes: A Randomized Controlled Trial (RUBAPRO)

Abstract: Background: The aim of this study is to demonstrate that a double balloon catheter combined with oxytocin decreases time between induction of labor and delivery (TID) as compared to a vaginal dinoprostone insert in cases of premature rupture of membranes at term. Methods: This is a prospective, randomized, controlled trial including patient undergoing labor induction for PROM at term with an unfavorable cervix in Clermont-Ferrand university hospital. We compared the double balloon catheter over a period of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
1
3
3
Order By: Relevance
“…Yan et al 12 and Du et al 3 reported that dinoprostone vaginal insert are more effective for labor induction than Cook's DBC, which could support our findings to some extent. In contrast, a randomized controlled trial on cases with rupture of membranes did not find any differences between dinoprostone and DBC plus oxytocin 13 . We speculate that population variation may be one of the main reasons for the discrepancy from our findings, because the present study focused mainly on Japanese pregnant women with intact membranes.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Yan et al 12 and Du et al 3 reported that dinoprostone vaginal insert are more effective for labor induction than Cook's DBC, which could support our findings to some extent. In contrast, a randomized controlled trial on cases with rupture of membranes did not find any differences between dinoprostone and DBC plus oxytocin 13 . We speculate that population variation may be one of the main reasons for the discrepancy from our findings, because the present study focused mainly on Japanese pregnant women with intact membranes.…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast, a randomized controlled trial on cases with rupture of membranes did not find any differences between dinoprostone and DBC plus oxytocin. 13 We speculate that population variation may be one of the main reasons for the discrepancy from our findings, because the present study focused mainly on Japanese pregnant women with intact membranes.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Анализ полученных результатов исследования показал, что наиболее часто подготовка шейки матки и родовозбуждение встречаются у первородящих женщин и наиболее частыми показаниями являются преждевременный разрыв плодных оболочек и тенденция к перенашиванию беременности, что совпадает с данными литературы [11][12][13][14].…”
Section: Discussionunclassified
“…The median DT was 8 hours faster for women who underwent early arti cial rupture than in women with expectant management [18]. Nevertheless, Eric Devillard et al compared a double balloon catheter with oxytocin versus a vaginal dinoprostone insert in women with PROM at term and found that there was no signi cant difference in DT between the two groups [19]. It would be interesting to explore the mechanism for the decreased DT, and we concluded that the decreased DT due to PROM was rarely related to the method of IOL.…”
Section: Discussionmentioning
confidence: 99%